Environmental severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) contamination in hospital rooms during the first and third coronavirus disease 2019 (COVID-19) waves - Killian Le Neindre; Jeanne Couturier; Aurélie Schnuriger; Sarah Jolivet; Cyril Gouot; Mickaël Majerholc; Pierre Supplisson; Céline Tan; Marine Perrier; Christelle Lazare; Laurence Morand-Joubert; Frédéric Barbut (Cambridge University Press, 2022)
We investigated the frequency, distribution, and risk factors of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) environmental contamination around infected patients during the first and third wave of the coronavirus disease 2019 pandemic. The shedding of SARS-CoV-2 in rooms of infected patients was limited in our hospital setting.